A geometrically exact composite thin-walled beam element for flexible multibody dynamics - Saravia, César Martín (2011)
A geometrically exact thin-walled composite beam finite element for multibody applications is presented. In the proposed formulation the virtual work equations are written as a function of generalized strains, which are parametrized in terms of the director field and its derivatives. Finite rotations are parametrized with the total rotation vector. The derivatives of the director field are obtained via interpolation, thus simplifying the linearization of the virtual strains. The material constitutive relations are based on the mechanics of composite laminates. The formulation of typical joints is briefly presented. The finite element is implemented in a multibody algorithm that uses the generalized-alpha method to integrate in time the differential-algebraic system of equations.